25th Anniversary Article: Carbon Nanotube‐ and Graphene‐Based Transparent Conductive Films for Optoelectronic Devices. (4th March 2014) - Du, Jinhong; Pei, Songfeng; Ma, Laipeng; Cheng, Hui‐Ming
<x xml:space="preserve">Abstract</x> Carbon nanotube (CNT)‐ and graphene (G)‐based transparent conductive films (TCFs) are two promising alternatives for commonly‐used indium tin oxide‐based TCFs for future flexible optoelectronic devices. This review comprehensively summarizes recent progress in the fabrication, properties, modification, patterning, and integration of CNT‐ and G‐TCFs into optoelectronic devices. Their potential applications and challenges in optoelectronic devices, such as organic photovoltaic cells, organic light emitting diodes and touch panels, are discussed in detail. More importantly, their key characteristics and advantages for use in these devices are compared. Despite many challenges, CNT‐ and G‐TCFs have demonstrated great potential in various optoelectronic devices and have already been used for some products like touch panels of smartphones. This illustrates the significant opportunities for the industrial use of CNTs and graphene, and hence pushes nanoscience and nanotechnology one step towards practical applications.